Hair styling based on eutectic formulations with peptides - Carvalho, Diana (2022)
Eutectic-based formulations were developed aiming to modify the shape and improve the mechanical properties of Asian hair. These formulations comprised a eutectic mixture (choline chloride and urea) as a solvent, a natural reducing agent (l-cysteine), and a decapeptide. The treatment of Asian hair with the eutectic-based formulations increased the resistance of hair to mechanical wear by about 10\\% when compared with hair treated with a styling commercial formulation (chemical treatment). For these samples, the change in hair shape is associated with the presence of cysteine and the decapeptide, which participates in the disruption and in the rearrangement of new disulfide bonds with the keratin fibers. The eutectic-based formulations here presented show great potential to be used as a new class of hair styling agents in haircare research. These new formulations will avoid/reduce the application of harsh chemicals, which induce irreversible damage in hair structure and have a negative impact on the environment.